Bovine Serum Albumin-Coated Niclosamide-Zein Nanoparticles as Potential Injectable Medicine against COVID-19 - Rejinold N, Sanoj (Materials (Basel), 2021)
(1) Background: COVID-19 has affected millions of people worldwide, but countries with high experimental anti-SARS-CoV-2 vaccination rates among the general population respectively show progress in achieving general herd immunity in the population (a combination of natural and vaccine-induced acquired immunity), resulting in a significant reduction in both newly detected infections and mortality rates. However, the longevity of the vaccines’ ability to provide protection against the ongoing pandemic is still unclear. Therefore, it is of utmost importance to have new medications to fight against the pandemic at the earliest point possible. Recently, it has been found that repurposing already existing drugs could, in fact, be an ideal strategy to formulate effective medication for COVID-19. Though there are many FDA-approved drugs, it has been found that niclosamide (NIC), an anthelmintic drug, has significantly high potential against the SARS-CoV-2 virus. (2) Methods: Here we deployed a simple self-assembling technique through which Zein nanoparticles were successfully used to encapsulate NIC, which was then coated with bovine serum albumin (BSA) in order to improve the drugs’ stability, injectablity, and selectivity towards the virus-infected cells. (3) Results: The particle size for the BSA-stabilized Zein-NIC nanohybrid was found to be less than 200 nm, with excellent colloidal stability and sustained drug release properties. In addition, the nanohybrid showed enhanced drug release behavior under serum conditions, indicating that such a hybrid drug delivery system could be highly beneficial for treating COVID-19 patients suffering from high endothelial glycocalyx damage followed by a cytokine storm related to the severe inflammations.